Karsinoma Nasofaring, Review - Muhammad Rosyidi, Rohadi; Kadriyan, Hamsu; Taufik, Ahmad; Zulkarnaen, Decky Aditya; Abdurrosid, Lalu Muhammad Kamal (LPPM Universitas Mataram, 2024)
Nasopharyngeal carcinoma is a malignancy that arises due to abnormal growth of body cells that appear in the nasopharyngeal area, namely the area above the throat and behind the nose. Almost 60% of malignant tumors of the head and neck are nasopharyngeal carcinomas, followed by malignant tumors of the nose and paranasal sinuses (18%), larynx (16%), and oral cavity tumors. Nasopharyngeal carcinoma is endemic in certain regions of the world, especially in Southeast Asia, and has a poor prognosis, with the highest incidence in southern China. Indonesia is one of the countries with a high prevalence of nasopharyngeal cancer patients. The average prevalence recorded is 6.2 cases per 100,000 Indonesian population with 13,000 new cases of nasopharyngeal carcinoma each year.